Population Dynamics of Bullet Tuna (Auxis rochei Risso 1881) from the Indian Ocean, West Nusa Tenggara, Indonesia - Evron Asrial; Ruly Isfatul Khasanah; Fathurriadi Fathrurriadi; Yasir Arapat; Usma Kurniawan Hadi; Lalu Achmad Tan Tilar Wangsajati Sukmaring Kalih; Lalu Samsul Rizal; Mita Ayu Liliyanti; Erwin Rosadi; Daduk Setyohadi; Muhammad Junaidi; Ishani Nelunika Rathnayake (Jurnal Ilmiah Perikanan dan Kelautan, 2021)
Highlight Research:The bullet tuna (Auxis rochei) was identified and analysed.The length at first maturity (Lm) of bullet tuna (Auxis rochei) was analyzedThe eligibility status of bullet tuna (Auxis rochei) has been analyzed and estimatedThe LWR curve can be used to estimate age groups of fish compared to the sigmoid curveThe CF cannot be automatically used to estimate fish worth selling AbstractThe bullet tuna (Auxis rochei), BLT or tongkol lisong (Indonesian) is a species of neritic tuna which is one of the target fish for small scale fishers. The problem of bullet tuna fisheries was that it has reached overexploitation and the immature bullet tuna are still caught. This study aimed to assess the population dynamics of the BLT and its size composition caught by small scale fishers in the Indian Ocean, West Nusa Tenggara area was carried out in Bangko-Bangko (West Lombok), Cemplung Beach (South Sumbawa) and Tanjung Luar Fishing Port (East Lombok) between July 2019 and June 2020. The data was derived from the measurement and weighing results of 1,217 BLT collected from the respective collector traders at each sampling location. The growth pattern of BLT was isometric () which meant the ideal body shape (mesomorph) and length at first maturity (FLm) was 31.11 cm. The length-weight relationship curve showed that BLT was in an immature age group (adolescent fish). Meanwhile, the composition of BLT is worth selling (Condition Factor > 1.00), fit for catch (FLc / FLm > 1.00) and worthy of maturity (FLc > FLm), respectively 99.92%, 0.82% and 0.00%. The BLT fish composition indicates that the stocks of resources and populations do not support current sustainable fisheries management.